The Morphopragmatics of the Diminutive Morpheme (-ba/-wa) in Akan - Clement K. I. Appah; Nana Aba Appiah Amfo (Lexis: Journal in English Lexicology)
The present paper is concerned with the diminutive morpheme -wa/-ba in Akan. It examines the form, the origin and the various meanings associated with diminutive forms in the language. We attribute the origin of the diminutive to the lexical word for ‘child/offspring’ ɔba, basing our argument on language internal evidence as well as cross-linguistic generalizations. The identified meanings of the Akan diminutive are as follows: small, young/offspring, feminine, member, insignificant/nonserious, affection/admiration and contempt/disdain. Having identified the basic meaning of the diminutive as ‘small’, Jurafsky’s [1996] Radial Category theory provides us with a basis to adequately account for the various meanings; drawing a link, through metaphors and inferences, between the diachronic and the synchronic meanings.